Unravelling mutational signatures with plasma circulating tumour DNA - Sebastian Hollizeck; Ning Wang; Stephen Q. Wong; Cassandra Litchfield; Jerick Guinto; Sarah Ftouni; Richard Rebello; Sehrish Kanwal; Ruining Dong; Sean Grimmond; Shahneen Sandhu; Linda Mileshkin; et al. (Nature Communications)
Abstract The use of circulating tumour DNA (ctDNA) to profile mutational signatures represents a non-invasive opportunity for understanding cancer mutational processes. Here we present MisMatchFinder, a liquid biopsy approach for mutational signature detection using low-coverage whole-genome sequencing of ctDNA. Through analysis of 375 plasma samples across 9 cancers, we demonstrate that MisMatchFinder accurately infers single-base and doublet-base substitutions, as well as insertions and deletions to enhance the detection of ctDNA and clinically relevant mutational signatures.